2020
DOI: 10.1002/jper.20-0645
|View full text |Cite
|
Sign up to set email alerts
|

Healing of donor sites of connective tissue grafts harvested by the single incision technique: A randomized clinical trial evaluating the use of collagen hemostatic sponge with or without sutures

Abstract: Background:The aim of this study was to evaluate the effect of suturing on the early wound healing of donor sites of subepithelial connective tissue grafts (SCTG), harvested by the single incision technique (SIT), following the application of a collagen sponge.Methods: Thirty-six patients were randomized to receive a collagen sponge with or without sutures in the palatal donor sites following connective tissue grafting via the SIT. Outcome variables were early healing index (EHI) at 7, 14, and 30 days, self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Schinini et al. (2021) showed that sutured and non‐sutured sites treated with collagen hemostatic sponges display similar pain control. Inferior results in pain control were obtained with a collagen hemostatic sponge in comparison to Alvogyl in one study (Ehab et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Schinini et al. (2021) showed that sutured and non‐sutured sites treated with collagen hemostatic sponges display similar pain control. Inferior results in pain control were obtained with a collagen hemostatic sponge in comparison to Alvogyl in one study (Ehab et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to L-PRF, lower pain levels were obtained for L-PRF in comparison to collagen hemostatic sponge in three studies (Femminella et al, 2016;Hassan et al, 2020;Sousa et al, 2020), however, collagen hemostatic sponge promoted more less levels of pain in comparison to L-PRF in one case series (Belkhede et al, 2019). Schinini et al (2021) showed that sutured and non-sutured sites treated with collagen hemostatic sponges display similar pain control. Inferior results in pain control were obtained with a collagen hemostatic sponge in comparison to…”
Section: Collagen Agentsmentioning
confidence: 94%
See 1 more Smart Citation
“…This material has shown numerous advantages, providing mechanical protection and establishing a matrix for clot formation and organization [7,17]. In addition, the use of a collagen sponge decreases the time to achieve hemostasis of the palatal wound [7] and produces early healing of connective tissue graft donor sites [18]. Recently, studies of the postoperative pain following graft harvesting procedures have combined collagen sponges with other products, such as cyanoacrylate tissue adhesive, to enhance the effect.…”
Section: Introductionmentioning
confidence: 99%